The association between ESG and the cost of debt : Evidence from publicly listed companies in the Nordics - Välilä, Sanni (My University, 2024)
Tighter regulation and increasing pressure from stakeholders have increased the importance of environmental, social and governance (ESG) factors in business strategy. Effective ESG practices increase transparency and reduce information asymmetries, which can bring economic benefits to companies, such as improved loan terms. As awareness and concern about ESG issues continue to grow, banks and financial institutions are being driven to incorporate ESG assessments into credit ratings in order to reduce the potential financial and reputational risks. While the significance of ESG factors is increasingly acknowledged, a research gap remains in understanding the association between ESG and the cost of debt, especially in the Nordic region. The Nordic countries are known for their strict ESG regulations and comprehensive reporting standards, which creates a unique basis for investigating whether better ESG performance is associated with economic benefits such as lower borrowing costs. The existing literature on the relationship between ESG performance and the cost of debt financing primarily centers on the US, India, and China. In addition, previous studies have generally examined the impact of overall ESG performance, while the impact of individual pillars has been overlooked. The aim of this thesis is to investigate whether there is a negative association between ESG performance and cost of debt for 440 publicly listed Nordic companies from 2011 to 2020. An ordinary least squares regression model was employed to analyze data, revealing a statistically significant negative correlation between overall ESG performance and the cost of debt. This finding supports the hypothesis that companies with stronger ESG performance tend to benefit from lower cost of debt. Further examination explored the association of individual ESG pillars and the cost of debt. The social pillar exhibited the strongest significant negative correlation with the cost of debt, suggesting that robust social practices are particularly influential in securing favorable loan terms. Environmental and governance pillars also demonstrated negative correlations, but with smaller magnitudes, highlighting the varied influences of the different ESG aspects. Robustness tests were conducted to strengthen the credibility of the findings. These tests explored factors like industry classification, mandatory ESG reporting regulations, and the lagged effect of ESG existence on the cost of debt. This study highlights the potential financial benefits of strong ESG performance, suggesting companies can use ESG as a strategic tool to reduce borrowing costs. However, limitations include data availability and a specific period and region. Future research could explore long- term financial impacts or how lenders integrate ESG into loan pricing.

Tiukentunut sääntely ja sidosryhmien kasvava paine ovat lisänneet ympäristöön, yhteiskuntaan ja hallintotapaan (ESG) liittyvien tekijöiden merkitystä liiketoimintastrategiassa. Tehokkaat yritysten yhteiskuntavastuukäytännöt lisäävät avoimuutta ja vähentävät tiedon epäsymmetriaa, mikä voi tuoda yrityksille taloudellista hyötyä, kuten parempia lainaehtoja. ESG-kysymysten kasvava tietoisuus ja huoli ovat ajaneet pankit ja rahoituslaitokset integroimaan ESG-arviointeja luottoluokituksiinsa. Tämän avulla rahoituslaitokset pyrkivät minimoimaan yhteiskuntavastuuseen liittyviä mahdollisia taloudellisia ja maineeseen liittyviä haittoja. Vaikka ESG-tekijöiden merkitys tunnustetaan yhä useammin, niiden vaikutuksesta velan kustannuksiin on edelleen tutkimusvajetta erityisesti Pohjoismaissa. Pohjoismaat ovat tunnettuja tiukoista ESG-säädöksistään ja kattavista raportointistandardeistaan, mikä luo ainutlaatuisen perustan tutkia, liittyykö parempi ESG-toiminta taloudellisiin hyötyihin, kuten alhaisempiin lainakustannuksiin Pohjoismaissa. ESG-suorituskyvyn ja velkarahoituksen kustannusten välistä suhdetta käsittelevät tutkimukset keskittyvät pääasiassa Yhdysvaltoihin, Intiaan ja Kiinaan. Lisäksi aiemmissa tutkimuksissa on yleensä tarkasteltu ESG-toiminnan kokonaisvaikutusta, kun taas yksittäisten pilarien vaikutus on jäänyt huomiotta. Tämän tutkielman tavoitteena on selvittää, onko ESG-suorituskyvyn ja velkarahoituksen kustannusten välillä negatiivinen yhteys 440 julkisesti noteeratun pohjoismaisen yrityksen osalta vuosina 2011–2020. Aineiston analysointiin käytettiin tavallista pienimmän neliösumman regressiomallia, joka paljasti tilastollisesti merkitsevän negatiivisen korrelaation ESG-toiminnan kokonaissuorituskyvyn ja velkarahoituksen kustannusten välillä. Tämä havainto tukee hypoteesia, jonka mukaan yritykset, joiden ESG-suorituskyky on parempi, hyötyvät yleensä alhaisemmista velkakustannuksista. Lisäksi tutkittiin yksittäisten ESG-pilarien ja velkarahoituksen kustannusten välistä yhteyttä. Sosiaalinen pilari korreloi voimakkaimmin ja velkarahoituksen kustannusten kanssa, mikä viittaa siihen, että vankat sosiaaliset käytännöt vaikuttavat erityisen paljon suotuisten lainaehtojen varmistamiseen. Ympäristö- ja hallintotapapilarit osoittivat myös negatiivista korrelaatiota, mutta pienemmällä voimakkuudella, mikä korostaa eri ESG-näkökohtien vaihtelevaa vaikutusta. Tulosten uskottavuuden vahvistamiseksi tehtiin täydentäviä analyyseja. Näissä testeissä tutkittiin toimialaluokitusta, pakollisia ESG-raportointisäännöksiä sekä ESG-suorituskyvyn viivästynyttä vaikutusta velkarahoituksen kustannuksiin. Tässä tutkimuksessa korostetaan vahvan ESG-suorituskyvyn mahdollisia taloudellisia hyötyjä, mikä viittaa siihen, että yritykset voivat hyödyntää yhteiskuntavastuullisuutta strategisena välineenä vähentääkseen velkarahoituksen kustannuksia. Tulevaisuuden tutkimuksissa voitaisiin tutkia pitkän aikavälin taloudellisia vaikutuksia tai kuinka lainanantajat sisällyttävät yhteiskuntavastuullisuuden lainojen hinnoitteluun.
Keywords: corporate responsibility; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|